The Effect of Flipped learning strategy on cognitive and practical learning of physical exercises and the development of deductive thinking among students of the of Physical Education and Sports Sciences - Prof. Dr. Jamal Shukri Bassim.; Prof. Dr. Silwan Khaled Mahmoud.; Assist. Prof. Dr. Zeyad Salim Alqarani. (Zien Journals, 2023)
The research aims to identify the impact of the flipped learning strategy on the cognitive and practical achievement of physical exercises and the development of deductive thinking among students of the College of Physical Education and Sports Sciences at the University of Mosul. The research community is made up of third year students for the academic year (2020-2021).The samples are chosen randomly, They represent the two groups (H), the experimental group, (and the control group), and the researchers have used the experimental method as a way to solve the research problem by designing equal groups with two pre- and post-tests. The prepared educational program took (6) weeks, as it include many educational activities based on the steps of the flipped education strategy. The most important results of the research are the effectiveness of the flipped learning strategy in the cognitive learning of physical exercises among third-year students in the College of Physical Education and Sports Sciences, as well as its effectiveness in the practical learning of physical exercises. The strategy work on developing deductive thinking, so the researchers recommended the necessity of Adopting the flipped learning strategy in teaching the concepts of physical education teaching methods.
Keywords: flipped teaching; cognitive learning; practical learning; deductive thinking